Tourism, Financial Development and Sectoral Development in ECOWAS Countries: Empirical Evidence from the CS-ARDL Approach - Séraphin, Prao Yao; Cyrille, Kongoza Kouassi (International Journal of Economics and Financial Issues, 2024)
This study examines the role of financial development in the relationship between tourism and sectoral development in 12 ECOWAS countries over the period 2003-2020. Methodologically, it mobilized the Cross-sectional Augmented Autoregressive Distributed Lag (CS-ARDL) model developed by Chudik and Pesaran (2015), which takes cross-sectional dependence and heterogeneity into account. The results reveal that tourism hurts the development of the agricultural and industrial sectors in both the short and long term. Financial development harms the agricultural sector, while it improves the development of the industrial sector in both the short and long term. On the other hand, tourism associated with a developed financial sector improves the development of the agricultural sector and also the industrial sector. This result suggests that the contribution of tourism to sectoral development in ECOWAS countries depends on the level of financial development.